Benign Medullary Fibroma of the Kidney: A Rare Diagnostic Dilemma - Kumar, Santosh; Choudhary, Gautam Ram; Nanjappa, Bhuvanesh; Bal, Amanjit
Renomedullary interstitial cell tumor or medullary fibroma, is a small tumor that commonly presents as an incidental finding, but in rare cases maybe large and symptomatic. Although it is a benign tumor, it is difficult to differentiate this lesion from other malignancies of the kidney on radiological basis and hence many patients undergo radical nephrectomy. We present a case of renal medullary fibroma and various nuances associated with radiological identification of this lesion and its management related dilemmas.